2018
DOI: 10.1200/po.18.00037
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features of Non–Small-Cell Lung Cancer Harboring an NTRK Gene Fusion

Abstract: Purpose Gene rearrangements involving NTRK1/2/3 can generate fusion oncoproteins containing the kinase domains of TRKA/B/C, respectively. These fusions are rare in non-small cell lung cancer (NSCLC), with frequency previously estimated to be <1%. Inhibition of TRK signaling has led to dramatic responses across tumor types with NTRK fusions. Despite the potential benefit of identifying these fusions, the clinicopathologic features of NTRK fusion-positive NSCLCs are not well characterized. Methods We compiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 22 publications
2
135
1
1
Order By: Relevance
“…Several drugs are the subject of clinical trials, and at least two of them are approved or in the process of approval: larotrectinib (LOXO-101, a selective inhibitor) and entrectinib (also a ROS1 and ALK inhibitor) [78]. There is a very small proportion of lung carcinoma patients (especially with adenocarcinomas) that present rearrangements in NTRK1, NTRK2 or NTRK3 [79]. Although early studies showed higher percentages, recent publications suggest a prevalence of less than 1% [78].…”
Section: Ntrkmentioning
confidence: 99%
“…Several drugs are the subject of clinical trials, and at least two of them are approved or in the process of approval: larotrectinib (LOXO-101, a selective inhibitor) and entrectinib (also a ROS1 and ALK inhibitor) [78]. There is a very small proportion of lung carcinoma patients (especially with adenocarcinomas) that present rearrangements in NTRK1, NTRK2 or NTRK3 [79]. Although early studies showed higher percentages, recent publications suggest a prevalence of less than 1% [78].…”
Section: Ntrkmentioning
confidence: 99%
“…The 5-year survival rate in metastatic disease is only 4.7%, making lung cancer the number one cause of cancer deaths globally. 1,2 In current practice, all patients with locally advanced or metastatic NSCLC (nonsquamous type) should be tested for pathogenic driver mutations in EGFR, 3,4 BRAF, [5][6][7] ERBB2, 8,9 KRAS, 10,11 and MET (including exon 14 skipping) [12][13][14][15] ; amplifications in EGFR, 16,17 ERBB2, and MET 12 ; fusions in RET, [18][19][20] ALK, [21][22][23] NTRK, 24,25 and ROS1 26,27 ; and for programmed death-ligand 1 (PD-L1) expression. [28][29][30][31] This is especially important in NSCLC in nonsmokers, who, as a group, are a distinct molecular entity harboring different driver mutations.…”
Section: Introductionmentioning
confidence: 99%
“…As for lung cancer, in a study in 4872 patients at 7 institutions, NTRK fusions were found in 11 patients (0.23%). Of them, six patients (55%) were male, eight patients (73%) were non-smokers/light smokers, and the median age was 47.6 years [30]. Nine of the 11 patients had adenocarcinoma.…”
Section: Frequency Of Ntrk Fusions By Cancer Typementioning
confidence: 99%